RESEARCHING FOOD-BORNE DISEASE AND THE LIFESTYLES OF THE STUDENTS AND FOOD HANDLERS IN RURAL SCHOOLS OF SARAWAK: A PRELIMINARY FINDINGS - Ling, Song Jing; Zamri, Hassan; Regina Garai, Abdullah (MALAYSIAN JOURNAL OF HEALTH PROMOTION (MJHP), 2021)
Food-borne diseases cause millions of deaths every year around the world. The major factors contributing to food-borne diseases and the prevalence of food poisoning among students are the food preparation process, lifestyles, physical cleanliness and water supplies. Food mismanagement by food handlers as well as the poor knowledge of students and food handlers on food hygiene are the factors that lead to food poisoning among school students. The objectives of this study are to : investigate how food handlers carry out food preparation; determine students’ and handlers’ standards of the food hygiene; assess the physical cleanliness of school canteens and the purity of their water supplies; and develop guidelines for the prevention of food poisoning. The aspects that are investigated in this study are the food preparation process, knowledge of food hygiene, physical cleanliness, and food poisoning prevention methods. The study was conducted in Sarawak and focused on students and food handlers. The current unprecedented Covid-19 pandemic and the rise of Covid-19 cases in Sarawak have caused local authorities to close the schools and there have been restrictions on inter-district travel under the government’s Conditional Movement Control Order (CMCO). The researcher thus decided to use questionnaires administered through Google Forms, WhatsApp’s, Computer-Assisted Telephone Interview (CATI) and Computer Assisted Personal Interview (CAPI). Quota sampling was adopted in selecting research participants. Indepth interviews, questionnaires and focus group discussions were the main data collection methods. The final outcome might be the creation of new knowledge related to food poisoning prevention and the findings may presumptively have implications on Malaysia’s health policy relating to food-borne diseases. Keywords: Food-borne diseases, food handlers, food preparation process, food poisoning prevention, physical cleanliness